Translating the Behaviour Change Technique Taxonomy Version 1 into Spanish: Methodology and Validation - Duarte-Anselmi, G; Fajardo-Cuevas, G (F1000 Research Ltd, 2024)
Background: Precise and unequivocal specification of intervention content is key to facilitating the accumulation and implementation of knowledge. The Behaviour Change Technique Taxonomy v1 (BCTTv1) is the most widely used classification of behaviour change techniques (BCTs), providing a shared, standardized vocabulary to identify the active ingredients of behavioural interventions. However, the BCTTv1 is only available in English and this hampers its broad use and adoption. The aim of the present article is to report the process of translation of the BCTTv1 into Spanish. Methods: A bilingual team led the translation of the BCTTv1, involving seven iterative steps: (i) establish a Committee, (ii) forward translation from English to Spanish, (iii) back translation from Spanish to English, (iv) comparison of original BCTTv1 and back translation, (v) opportunistic comparison against an independent BCTTv1 translation, (vi) empirical testing, and (vii) final Committee review. Results: Changes as a result of the translation process included relabelling BCTs, amending definitions, and fixing conceptual and grammatical inconsistencies, yielding the final version. Very satisfactory inter-coder reliability in BCT identification was observed as part of the empirical testing (i.e., prevalence and bias-adjusted kappa scores > 0.8). Conclusions: This work provides the Spanish-speaking population with a rigorous and validated BCTTv1 translation which can be used in both research and practice to provide a greater level of intervention detail for evidence synthesis, comparison, and replication of behaviour change interventions. The translation process described here may prove helpful to guide future translation efforts in behavioural science and beyond. ©: © 2024 Castro O et al.